Analyzing students’ visual attention through spy glasses - Farsani, Danyal (2022)
Visual attention is an important indicator in teacher-student interactions. This article presents the results of a study aimed to determine how the visual attention paid to the teacher by students fluctuates during their math and English classes and to detect possible differences in their attention.  The study was conducted in a secondary school with a sample of 16 male students.  Data was obtained by a mini video camera mounted on glasses wore by students. Using google images, we automatically and objectively analyzed 2613 frames from the recordings where the teacher appeared in the students’ visual field. Results show a difference in students’ visual attention between introvert and extrovert students throughout the 90-minute class. It was also observed that students were more visually engaged when the teacher's speech was accompanied by gestures. The paper highlights the importance of diversifying interactions that seek other ways to engage students in the last two-thirds of the class. Some implications for professional development programs are derived from this study.